2017
DOI: 10.1016/j.pmedr.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Household expenditures on dietary supplements sold for weight loss, muscle building, and sexual function: Disproportionate burden by gender and income

Abstract: Dietary supplements sold for weight loss (WL), muscle building (MB), and sexual function (SF) are not medically recommended. They have been shown to be ineffective in many cases and pose serious health risks to consumers due to adulteration with banned substances, prescription pharmaceuticals, and other dangerous chemicals. Yet no prior research has investigated how these products may disproportionately burden individuals and families by gender and socioeconomic position across households. We investigated hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This finding might reflect the fact that the high expenditure on HSPs was a burden to chronic disease patients with a low household income. A study by Austin et al (2017) also found that the cost of HSPs might place the low household income families at a higher risk of financial burden. Interestingly, household income was the only determining factor for the use of HSPs in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding might reflect the fact that the high expenditure on HSPs was a burden to chronic disease patients with a low household income. A study by Austin et al (2017) also found that the cost of HSPs might place the low household income families at a higher risk of financial burden. Interestingly, household income was the only determining factor for the use of HSPs in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The sales of HSPs in Malaysia was rapidly growing from USD 488 million in 2014 to USD 730 million in 2019 (Lim, 2020). Meanwhile, the expenditure recorded on HSP use in the United States was USD 36.7 billion in 2014, and USD 2 billion and USD 2.6 billion were specifically on supplements for weight loss and muscle building, respectively, in 2015 (Austin et al, 2017). Indeed, the use of HSPs was found among elderly people who consumed various prescription medications for multiple comorbid conditions (Bailey et al, 2010), as well as in children and adolescents (Liu et al, 2019;Mohammadbeigi et al, 2020;Namazi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive research emphasizes that lifestyle changes are required for successful weight loss, 1,2 each year millions of consumers turn to unproven over-the-counter weight loss supplements to "quick start" their weight loss attempts, hoping this time things will be different. 3,4 Below, we discuss the safety and efficacy of over-the-counter weight loss supplements and suggest ways clinicians can discuss weight loss with patients like Ms S.…”
Section: Casementioning
confidence: 99%
“…In addition, our results showed that the respondents who use supplements for weight loss and body weight control also combine them with products for physical and sport performance. However, the previous studies mentioned that dietary supplements used for weight loss, muscle building and sexual function are not medically recommended, have been shown to be ineffective in many cases and can represent a potential health risk for consumers (Austin et al, 2017;Salgado et al, 2014).…”
Section: Factors Influencing Consumers' Decision Tomentioning
confidence: 99%